PENGARUH E-WOM (Electronic Word Of Mouth) DAN DAYA TARIK TERHADAP KEPUTUSAN BERKUNJUNG REST AREA HERITAGE KM 260B - Annissa Atussholiha; Syariefful Ikhwan; Roby Setiadi (STEKOM PRESS, 2023)
This study has the main objective of knowing how the influence of E-WOM (electronic word of mouth) and the appeal of the decision to visit the Rest Area Heritage KM 260B. This study uses a quantitative research type with the SPSS version 22 method. The population used in this study is all visitors in the Heritage Rest Area with a sample of 101 respondents, consisting of 16 questions and obtained by distributing questionnaires to all Rest Area Heritage visitors. offline (paper) and online (google form). The results showed that the E-WOM variable had a positive effect on visiting decisions with a significance value (sig) of 0.000 < probability 0.05 and a tcount of 5,458 > ttable of 1,985. The attractiveness variable has a positive effect on the decision to visit with a significance value (sig) of 0.009 < probability 0.05 and a tcount of 2.667 > ttable of 1.985, so it can be interpreted that the variation of all independent variables, namely E-WOM and attractiveness can affect the decision to visit